The stability of diaphragm wall for deep excavation - Hamzah, Muhammad Hafizuddin; Mohd Taib, Aizat; Sharil, Suraya; Ramli, Ahmad Bukhari; Abang Hasbollah, Dayang Zulaika (World Academy of Research in Science and Engineering, 2019)
Rapid urbanisation and the increase in population has led to massive use of underground spaces, especially in the city. Before an underground structure is built, the use of retaining structure is crucial in order to prevent the excavation from failure. Diaphragm wall is a widely used retaining structure, particularly for deep excavation. A holistic understanding of the performance and its behaviour is essential to provide stability of the soil retained. A parametric study by using Plaxis2D has been conducted to determine the factors affecting the stability of diaphragm wall and the excavation sites in underground Mass Rapid Transit station of Hospital Kuala Lumpur (HKLX). The objectives of this study are to determine the effect of diaphragm wall stiffness, groundwater drawdown and the depth of wall for deep excavation. The stability is captured based on the lateral deflection of wall, bending moment, safety factor and ground movement near the diaphragm wall. From the study, it is found that the diaphragm wall with high stiffness can reduce wall deflection up to 20% with the addition of 49% bending moment and achieve a high factor of safety. Furthermore, groundwater drawdown is seen reducing lateral deflection of the wall up to 1.08% as well as increasing the factor of safety. Finally, decreasing wall depth reduces the wall deflection by 0.38% and also the basal heaving.